Pemberdayaan Wirausahawan Perempuan di Lingkungan Pesantren melalui Sistem Pemesanan Terjadwal: Sebuah Pendekatan Pengabdian Masyarakat Terstruktur - Rofiah, Chusnul; Widijanto , Sapto Roedy; Anam, Chairul (Unity Academy, 2025)
This community engagement program aims to strengthen pesantren-based entrepreneurship through a scheduled ordering system designed to meet the daily needs of female students. The system is managed collaboratively by caregivers and alumni of PPHQ Putri 1. This initiative serves as a strategic response to the limited entrepreneurial preparedness of pesantren alumni in addressing contemporary economic challenges, while also promoting community-based economic self-reliance. The program employed a participatory approach, incorporating entrepreneurship motivation sessions, personalized consultations, technical training in basic business management, and live implementation of an open pre-order service model. The activities were structured over two academic semesters (May–July 2025), covering stages such as student needs assessment, formation of operational teams, digital business recording training, and monthly business mentoring by university faculty. The results indicate a significant improvement in alumni entrepreneurial motivation, business mindset development, and concrete initiatives, including the formation of alumni-led business groups. Moreover, the scheduled ordering model proved effective in linking internal supply with actual student demand in a responsive and efficient manner. This initiative successfully demonstrated a replicable and structured model of pesantren-based entrepreneurship, grounded in real community needs and sustained through collaborative engagement.